1989
DOI: 10.1017/s0022215100109430
|View full text |Cite
|
Sign up to set email alerts
|

Role of irradiation in the suppression of parotid secretions

Abstract: Suppression of salivary flow is of value in the management of salivary fistulae and sialectasia. It may also be beneficial in mentally defective patients and those with neurological palsies lacking control of their salivation. Nine patients were treated by irradiation to the parotid gland to control salivary flow; eight had complete resolution of symptoms and one had partial relief. Irradiation was effective as primary treatment and after failed surgery and/or drug treatment. Low doses were effective and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…25 Two additional approaches may be considered when medical treatments fail. External beam irradiation (3 to 30 Gy, 3 to 10 fractions) to a single parotid gland may be effective in reducing sialorrhea, 26 but it has not been evaluated in ALS. Surgical intervention has been tried in patients with ALS.…”
Section: Symptom Management (Sialorrhea and Pseudobulbar Affect)mentioning
confidence: 99%
“…25 Two additional approaches may be considered when medical treatments fail. External beam irradiation (3 to 30 Gy, 3 to 10 fractions) to a single parotid gland may be effective in reducing sialorrhea, 26 but it has not been evaluated in ALS. Surgical intervention has been tried in patients with ALS.…”
Section: Symptom Management (Sialorrhea and Pseudobulbar Affect)mentioning
confidence: 99%
“…However in a retrospective case series of sialorrhea from various causes, including two with motor neuron disease, Borg et al concluded that the response rates in reducing saliva production was superior for patients treated with electron radiation N7 MeV, compared to those treated with conventional photon X-irradiation [13]. Previous small series reported suppression of sialorrhea with unilateral [14] or bilateral [15] parotid electron beam irradiation. Electrons allow for a more precise targeting of the superficial parotid glands [13,16], thereby reducing radiation exposure of the oral mucosa, mouth, and teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Chez des patients non atteints de SLA mais souffrant de sialorrhée médicamenteuse rebelle, on a pratiqué avec succès l'irradiation unilatérale de la parotide (3-30 Gray en 3-10 fractions [25]). L'injection de toxine botulinique dans les glandes salivaires peut réduire efficacement la production de salive pour une durée s'étendant jusqu'à 6 mois [26][27][28].…”
Section: Gestion Du Risque Pulmonaireunclassified